2013
DOI: 10.1016/j.cell.2013.04.053
|View full text |Cite
|
Sign up to set email alerts
|

Architectural Protein Subclasses Shape 3D Organization of Genomes during Lineage Commitment

Abstract: Summary Understanding the topological configurations of chromatin may reveal valuable insights into how the genome and epigenome act in concert to control cell fate during development. Here we generate high-resolution architecture maps across seven genomic loci in embryonic stem cells and neural progenitor cells. We observe a hierarchy of 3-D interactions that undergo marked reorganization at the sub-Mb scale during differentiation. Distinct combinations of CTCF, Mediator, and cohesin show widespread enrichmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

84
1,123
5
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,096 publications
(1,232 citation statements)
references
References 61 publications
(64 reference statements)
84
1,123
5
2
Order By: Relevance
“…These results agree with a study by Phillips-Cremins et al (2013) who investigated interactions in select regions of the mouse genome and found that > 80% of interactions were anchored by some combination of CTCF, MED12, or SMC1, a subunit of cohesin. Our analysis further revealed that CTCF and RAD21 were members of nearly every cobinding pattern that was enriched for interactions.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results agree with a study by Phillips-Cremins et al (2013) who investigated interactions in select regions of the mouse genome and found that > 80% of interactions were anchored by some combination of CTCF, MED12, or SMC1, a subunit of cohesin. Our analysis further revealed that CTCF and RAD21 were members of nearly every cobinding pattern that was enriched for interactions.…”
Section: Discussionsupporting
confidence: 82%
“…interactions (Kagey et al 2010;Hoffman et al 2013;Merkenschlager and Odom 2013;Phillips-Cremins et al 2013). CTCF, a canonical insulator protein, which is found at the majority (96.7%) of RAD21 sites in K562 cells, has also recently been implicated in long-range interactions (Handoko et al 2011).…”
Section: Genome-wide Map Of Regulatory Interactionsmentioning
confidence: 99%
“…The co-existence of two processes with different modes and scales of action can help explain the difficulties in the field in delineating and unambiguously classifying the different features of Hi-C maps, leading to a confusing plethora of denominations and definitions 7,8,12,4042 . Our data demonstrates clearly the existence of local, cohesin-dependent, self-interacting domains identifiable as TADs.…”
Section: Two Independent Folding Principlesmentioning
confidence: 99%
“…As evident from the literature and argued by Taberlay et al [27], the available genome-wide assays for chromatin conformation analyses are unreliable for interpreting connectivity at distances >100 kb. However, the chromatin occupancies of the cohesin complex, which facilitates enhancer-promoter looping, may infer such interactions [27][28][29]. Therefore, we assessed the occupancy of Rad21, a member of cohesion complex, and Nipbl, a cohesin-loading factor.…”
Section: Dum Silences Dppa2 Expression Through Recruiting Dnmts To Itmentioning
confidence: 99%